A PRESENTATION FOR A SUBMONOID OF THE SYMMETRIC INVERSE MONOID - Apatsara Sareeto; Jörg Koppitz (Ural Mathematical Journal)
In the present paper,  we study a submonoid of the symmetric inverse semigroup \(I_n\). Specifically, we  consider the monoid of all order-, fence-, and parity-preserving transformations of \(I_n\). While the rank and a set of generators of minimal size for this monoid are already known, we will provide a presentation for this monoid.